The Evolution of Digital Humanities: Challenges and Opportunities - Mohapatra, Abinash (AG Volumes, 2025)
One of the roots and main pillars of the digital humanities field, which aids in the development of solutions to handle enormous volumes of cultural heritage data—text being the primary data type—is the transition from studying a single book "on paper" to having the ability to browse numerous digital texts in this day and age. A survey of the literature on the prospects and problems in the field of digital humanities is presented in this article. This review reveals that digital humanities, while rich in interdisciplinary potential, face challenges including limited technical expertise among humanities scholars, inadequate theoretical grounding, and concerns over digital material authenticity and sustainability. Despite these issues, digital humanities enhance cultural preservation, access to knowledge, and collaborative global research. Libraries play a pivotal role, with changing librarian skill sets being central to implementation success. Gaps remain in exploring the roles of librarians in academic settings. Moving forward, research must focus on sustainability, training, and institutional support. Overall, digital humanities offer vast opportunities, provided challenges are actively addressed and managed collaboratively.